2015
DOI: 10.3892/mco.2015.599
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of complete removal of colorectal cancer with synchronous lung metastases

Abstract: Abstract. The prognosis-improving effect of radical surgery has been demonstrated in patients with colorectal cancer (CRC) with liver metastases. However, few studies have examined the effectiveness of treatments for CRC with metastases in organs other than the liver. The aim of the present study was to evaluate the outcome of surgical treatment for CRC with lung metastases. The study retrospectively examined 57 primary CRC patients (28 men, median age of 65 years) with synchronous lung metastases who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…22 Lung metastasectomy was indicated only for patients in whom all lung metastases (generally up to five metastases) could be removed with adequate surgical margins and future respiratory function based on mutual consent among members of a multidisciplinary team conference. 1,6,23 The basic procedure of lung resection was wedge resection, while lobectomy was performed if lung metastases were located in the deep parenchyma. 6 Regardless of the tumor number, size, and distribution, surgical resection was indicated for patients who met the above-mentioned criteria.…”
Section: Treatment Strategymentioning
confidence: 99%
“…22 Lung metastasectomy was indicated only for patients in whom all lung metastases (generally up to five metastases) could be removed with adequate surgical margins and future respiratory function based on mutual consent among members of a multidisciplinary team conference. 1,6,23 The basic procedure of lung resection was wedge resection, while lobectomy was performed if lung metastases were located in the deep parenchyma. 6 Regardless of the tumor number, size, and distribution, surgical resection was indicated for patients who met the above-mentioned criteria.…”
Section: Treatment Strategymentioning
confidence: 99%
“…Shimizu et al (80) recently analyzed the outcomes of PM in patients with a history of liver metastases and showed that a high preoperative CEA level was an independent prognostic factor for the overall survival. Although there have been only a few reports on PM for patients with both pulmonary and hepatic metastases detected simultaneously with the primary tumor, PM for such patients was still shown to provide favorable long-term outcomes (81,82). However, a history of distant metastases other than to the liver is believed to be a poor prognostic factor (72,79).…”
Section: Prognostic Factors For Each Tumor Type Crcmentioning
confidence: 99%
“…[3,4] Some studies observe that primary tumor resection (PTR) without metastasectomy has no superiority to palliative stoma surgery. [5,6] Another SEER-based study shows a trend toward fewer PTS from 1988 to 2010 with better survival. [7] However, there are still other studies a rming the effectiveness of PTR, especially which present with related symptoms.…”
Section: Instructionmentioning
confidence: 99%